Criminal Law Protection to the Right to Privacy in the Utilization of Digital Technology - Andreas Eno Tirtakusuma; Eleazar Josiah Tirtakusuma (International Journal of Law Reconstruction, 2025)
The rapid development of digital technology, including artificial intelligence, has brought tremendous progress for human rights, but also a real threat to privacy, where states and companies can now easily track, analyze, predict, and even manipulate people’s behavior on a massive scale such as through wiretapping, surveillance, or police raids related to online gambling without strict safeguards, which risks undermining individual dignity, autonomy, and rights. Therefore, this study aims to examine and formulate an ideal concept for protecting privacy rights within the confines of Indonesian criminal law, particularly amidst rapid technological evolution. The method used is normative legal research with a juridical and philosophical approach, to identify various laws and philosophies related to privacy protection in the criminal realm, while delving into the legal issues in depth. The results reveal that existing regulations still need to be supported by the theory of privacy as a human right and the concept of law as a protective sword and shield. In conclusion, the ideal concept must integrate these principles into the Indonesian legal framework, so that technology remains a driver of progress without sacrificing citizens’ privacy.